Cutaneous mucormycosis in advanced HIV disease - Moreira,José (2016)
ABSTRACT Angionvasive mucormycosis is an emerging fungal disease known to affect mainly diabetics or subjects with profound neutropenia. Infection usually occurs through the inhalation route, but cutaneous inoculation may occur after trauma or burns. However, mucormycosis remains unusual in HIV infection. We report a fatal case of cutaneous mucormycosis due to Rhizopus arrhizus involving the scalp following herpes zoster infection. The patient was a 42-year-old man with advanced AIDS failing on salvage antiretroviral therapy. The fungus was diagnosed on the basis of histopathology and culture. Our case emphasizes the need to consider mucormycosis in the differential diagnosis of necrotic cutaneous lesions in patients with late-stage HIV disease.